Polyphenol Bioaccessibility and Sugar Reducing Capacity of Black, Green, and White Teas - Shelly Coe; Ann Fraser; Lisa Ryan (International Journal of Food Science)
Tea (Camellia sinensis) is a widely consumed beverage and recognised for its potential enhancing effect on human health due to its rich polyphenol content. While a number of studies have investigated the quantity and type of polyphenols present in different tea samples, no study has reported the potential effect of digestive enzymes on the availability of tea polyphenols for human absorption or the subsequent impact on glycaemic response. The objectives of the present study were to assess the total polyphenol content of different teas, to assess the bioaccessibility of polyphenols in whole and bagged teas, and to determine the effect of black, white, and green tea infusions on sugar release. All of the teas were a significant source of polyphenols (10–116 mg Gallic acid equivalents/g). There was an overall increase in the release of polyphenols from both the bagged and the whole teas following in vitro digestion. Bagged green tea significantly () reduced rapidly digestible starch from white bread samples compared to control and black and white bagged teas. The present study confirms that tea is a rich source of polyphenols and highlights the potential benefits it may have on modulating glycaemic response in humans.